Long-term consumption of green tea protects the mental health of middle-aged and older adult men by improving inflammation levels - Wan, Zhenyu; Wan, Qirong; Qin, Xucong; Wang, Gaohua; Lin, Hong; Jin, Yong; Wan, Bing; Ai, Linfeng; Wei, Juan (Frontiers in Public Health, 2025)
BackgroundMiddle-aged and older adult men are at a heightened risk of depression. Green tea, as a popular beverage, has drawn widespread attention for its health benefits. However, there remains controversy over the effects of green tea on combating depression and regulating hormones.ObjectiveThis study aimed to investigate the effects of long-term green tea consumption on depression levels, hormones, and brain structure in, middle-aged and older adult men.MethodsA total of 280 volunteers participated in the study, divided into a tea-drinking group and a control group. Basic demographic information and biological marker data, as well as MRI data from some of the volunteers, were collected. A controlled study was conducted to explore the effects of long-term tea drinking on them.ResultsBMI (p = 0.002), depression level (p = 0.003), insomnia severity (p = 0.008), and systemic inflammation index (p = 0.009) were significantly lower in the tea drinking group, and their testosterone levels were significantly higher than those in the control group (p = 0.001). Moreover, GM volume in the right precuneus in the control group was significantly reduced compared with that in the tea drinking group.ConclusionLong-term tea consumption helps reduce BMI and increase testosterone levels in middle-aged and older adult men, and it can also reduce their risk of depression by lowering inflammation and improving sleep quality. Additionally, long-term tea consumption may have the potential to delay brain aging in middle-aged and older adult men.